Upscaling groundnut seed production and delivery through long-term public–private and development organization partnerships : Experiences from Tanzania - Hatibu, Asha Ally; Akpo, Essegbemon; Lukurugu, Gerald Alex; Nzunda, Joseph; Okori, Patrick; Ojiewo, Christopher Ochieng (MDPI, 2023)
Making quality seed of improved legume varieties sustainably available and accessible to farmers in a timely manner and at affordable price is a major challenge in sub-Saharan Africa (SSA). Overcoming this challenge requires collective and long-term action through public–private and development organization partnerships (PPDOPs). The PPDOP model was tested by key seed system actors under the Tropical Legumes (TL) and Accelerated Varietal Improvement and Seed Delivery of Legumes and Cereals in Africa (AVISA) projects from 2008 to 2021. The study used the case of groundnut in Tanzania to assess the role played by long-term PPDOPs in groundnut seed production and delivery systems. The effectiveness of seed production and delivery models of the various actors involved in the TL and AVISA projects was analyzed. The study used secondary data obtained from annual reports, unpublished and published literature, and institutional websites. The PPDOP model brought about significant changes to the seed systems. It was found that sustained seed production and delivery over a decade enhanced the performance of the groundnut value chain in Tanzania. Under the TL and AVISA projects, a total of 49,046 tons of groundnut from different seed classes were produced through PPDOPs, covering an estimated 613,078 hectares with improved groundnut varieties. The intervention reached 45,201 stakeholders through 3048 demonstration plots, 128 field days, 55 seed fairs, and 8147 tons of small seed packs of 1–5 kg. The study recommends the use of long-term PPDOPs in seed production and delivery systems for greater impacts on increased variety adoption and consistent seed supply and availability in SSA. Long-term PPDOPs ensure proper coordination, open communication, clear accountability, solid trust, and standardized practices among actors in seed production and delivery systems.